Yield of Adding chest CT to Abdominal CT to Detect COVID-19 in Patients Presenting With Acute Gastrointestinal Symptoms (SCOUT-3): Multicenter Study. Issue 6 (18th December 2022) - Borgstein, A.B.J.; Scheijmans, J.C.G.; Puylaert, C.A.J.; Keywani, K.; Lobatto, M.E.; Orsini, R.G.; van Rees Veillinga, T.; van Rossen, J.; Scheerder, M.J.; Voermans, R.P.; Han, A.X.; Russell, C.A.; et al.
Abstract : Objective: To determine the incremental yield of standardized addition of chest CT to abdominal CT to detect COVID-19 in patients presenting with primarily acute gastrointestinal symptoms requiring abdominal imaging. Summary Background Data: Around 20% of patients with COVID-19 present with gastrointestinal symptoms. COVID-19 might be neglected in these patients, as the focus could be on finding abdominal pathology. During the COVID-19 pandemic, several centers have routinely added chest CT to abdominal CT to detect possible COVID-19 in patients presenting with gastrointestinal symptoms. However, the incremental yield of this strategy is unknown. Methods: This multicenter study in 6 Dutch centers included consecutive adult patients presenting with acute nontraumatic gastrointestinal symptoms, who underwent standardized combined abdominal and chest CT between March 15, 2020 and April 30, 2020. All CT scans were read for signs of COVID-19 related pulmonary sequelae using the СО-RADS score. The primary outcome was the yield of high COVID-19 suspicion (СО-RADS 4-5) based on chest CT. Results: A total of 392 patients were included. Radiologic suspicion for COVID-19 (СО-RADS 4-5) was present in 17 (4.3%) patients, eleven of which were diagnosed with COVID-19. Only 5 patients with СО-RADS 4-5 presented without any respiratory symptoms and were diagnosed with COVID-19. No relation with community prevalence could be detected. Conclusion: The yield of adding chest CT to abdominal CT to detect COVID-19 in patients presenting with acute gastrointestinal symptoms is extremely low with an additional detection rate of around 1%.